The role of regulatory frameworks in shaping the firm value of cross-listed companies: a comparative analysis - Yi, Chen; Abdul Latiff, Ahmed Razman (Fayrel Management Services, 2024)
This study examines the impact of regulatory frameworks on the firm value of cross-listed companies in Hong Kong and Mainland China, employing Institutional and Agency theories as analytical lenses. The research primarily utilizes quantitative methodologies, analysing secondary data sourced from financial databases and regulatory bodies. Key findings indicate that stringent regulatory compliance in Hong Kong correlates with higher firm values compared to Mainland China. Effective enforcement of regulations in Hong Kong also reduces information asymmetry, thereby increasing firm value. Conversely, regulatory discrepancies between the two regions increase perceived investment risks, negatively impacting firm value. These results underscore the importance of robust, consistent regulatory practices in enhancing corporate legitimacy and investor confidence. The study acknowledges limitations related to the reliance on secondary data and the dynamic nature of regulatory frameworks, which may affect the timeliness and applicability of the findings across different regions. Future research directions include conducting longitudinal studies to assess the temporal effects of regulatory changes, incorporating qualitative analyses to deepen understanding of corporate responses to regulatory environments, and expanding the geographical scope to include comparisons with other global markets. This research contributes to the existing literature by highlighting how regulatory alignment and enforcement influence the economic valuation of cross-listed firms, providing valuable insights for regulators and corporate managers aiming to optimize firm value in complex regulatory landscapes.